(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine some factors related to the treatment effectiveness of the combined regimen of Hoang ky bo huyet thang and acupressure massage on patients with chronic cerebral circulatory insufficiency at Thai Binh provincial Hospital of Traditional Medicine. Method: A cross-sectional descriptive study was conducted on 30 chronic cerebral circulatory insufficiency patients treated at Thai Binh provincial Hospital of Traditional Medicine from May 2023 to December 2023 with Hoang ky bo huyet thang (1 decoction/day) combined with acupressure massage for 15 days. Results: The treatment effectiveness rated as good reached 80%. Factors significantly associated with good effectiveness included: female gender (OR = 25.0), absence of other chronic diseases (OR = 10.0), and duration of chronic cerebral circulatory insufficiency under 6 months (OR = 7.6) (p < 0.05). Conclusion: The combined regimen of Hoang ky bo huyet thang and acupressure massage demonstrated good treatment efficacy in the majority of chronic cerebral circulatory insufficiency patients. Female gender, absence of chronic comorbidities, and shorter disease duration are favorable prognostic factors for treatment effectiveness.